STRATEGI KPCPEN DALAM MEMBINA HUBUNGAN MEDIA PADA PENANGANAN COVID-19 TAHUN 2021 - Nofebri Tri Rusma Putra; Shabrina Hazhiya (Jurnal Ilmu Komunikasi Acta Diurna, 2023)
Maintaining a good relations with the media is very important for public relations (PR). Due to the media is used for publication where all information about the company is distributed, therefore it also means to build reputation. Currently the media is a reference for the public to move and act, the public seems following the media to behave in accordance with existing issues. If the media leads the public in a negative direction, this will have an unfavourable impact on the company because it can affect the company's reputation. This study aims to determine how KPCPEN's strategy in fostering media relations in handling Covid-19 in 2021, using descriptive qualitative research methods. Media relations is a part of public relations activities carried out in an organization, company, or government agency as a strategy in carrying out public relations/PR functions to achieve certain purposes.